A fine-scale recombination map of the human–chimpanzee ancestor reveals faster change in humans than in chimpanzees and a strong impact of GC-biased gene conversion - Munch, Kasper; Mailund, Thomas; Dutheil, Julien Y.; Schierup, Mikkel Heide

(untitled) (Genome Research, 2014)
Recombination is a major determinant of adaptive and nonadaptive evolution. Understanding how the recombination landscape has evolved in humans is thus key to the interpretation of human genomic evolution. Comparison of fine-scale recombination maps of human and chimpanzee has revealed large changes at fine genomic scales and conservation over large scales. Here we demonstrate how a fine-scale recombination map can be derived for the ancestor of human and chimpanzee, allowing us to study the changes that have occurred in human and chimpanzee since these species diverged. The map is produced from more than one million accurately determined recombination events. We find that this new recombination map is intermediate to the maps of human and chimpanzee but that the recombination landscape has evolved more rapidly in the human lineage than in the chimpanzee lineage. We use the map to show that recombination rate, through the effect of GC-biased gene conversion, is an even stronger determinant of base composition evolution than previously reported.